2020
DOI: 10.1007/s10654-020-00621-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal healthful dietary patterns during peripregnancy and long-term overweight risk in their offspring

Abstract: Adherence to healthful dietary patterns is associated with lower body mass index (BMI) in adults; however, whether maternal diet quality during peripregnancy is related to a lower overweight risk in the offspring remains to be elucidated. We investigated the associations between the Alternate Healthy Eating Index (AHEI), Alternate Mediterranean Diet (aMED) and Dietary Approach to Stop Hypertension (DASH) during peripregnancy and offspring weight outcomes in a study including 2729 mother-child pairs from the Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
(70 reference statements)
1
20
2
Order By: Relevance
“…To our knowledge, this is the first evidence conducted on the association between preconception diet quality and offspring BMI outcomes in Australia. Our finding is contrary to that of Strohmaier et al (2020) who found no relationship between healthful dietary intake during peri-conception and offspring obesity aged 12–23 years [ 19 ]. This inconsistency might be due to the difference in quality and quantity of maternal diets, the timing of the intake, offspring age, and the assessment techniques used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first evidence conducted on the association between preconception diet quality and offspring BMI outcomes in Australia. Our finding is contrary to that of Strohmaier et al (2020) who found no relationship between healthful dietary intake during peri-conception and offspring obesity aged 12–23 years [ 19 ]. This inconsistency might be due to the difference in quality and quantity of maternal diets, the timing of the intake, offspring age, and the assessment techniques used.…”
Section: Discussioncontrasting
confidence: 99%
“…A considerable amount of literature has been published on the relationship between maternal diet in pregnancy and childhood body compositions or BMI outcomes, including overweight and obesity; however, the findings have been inconsistent [ 15 , 16 , 17 , 18 ]. A prospective cohort study conducted by Strohmaier et al reported no association between peri-conception healthy dietary patterns and obesity risk in their offspring [ 19 ]. No study, to our knowledge, has conducted the relationship between pre-pregnancy diet quality and a child’s BMI outcomes in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of results from the Growing Up Today Study II across follow-up ages of 12–23 years indicate that greater maternal adherence to the Alternate Mediterranean Diet (aMED) score (adapted to the US population) showed similar findings with a lower risk of offspring overweight or obesity [ 116 ]. However, the results were not significant following adjustment for potential confounders including maternal pre-pregnancy BMI and lifestyle factors.…”
Section: Maternal Dietary Metrics and Offspring Childhood Outcomesmentioning
confidence: 99%
“…However, the results were not significant following adjustment for potential confounders including maternal pre-pregnancy BMI and lifestyle factors. It should be noted that childhood weight measures were self-reported in the study, which may lead to underreporting amongst adolescents with obesity [ 116 ]. In a Spanish study predicting long-term health outcome risks, the importance of tracking childhood adiposity rather than crude weight alone is underscored, because cardiometabolic risk factors are more prevalent in children and adolescents with abdominal obesity than those with general overweight/obesity [ 121 , 124 , 125 ].…”
Section: Maternal Dietary Metrics and Offspring Childhood Outcomesmentioning
confidence: 99%
See 1 more Smart Citation